CONCEPTION PROPOSAL OF ORGANIZATION OF AFTER-SCHOOL CARE CENTERS IN RELATION TO TEACHING OF TECHNOLOGIES - TVARUZKA, Vaclav (Trends in education, 2009)
After-school care centers are the most numerous institutions that have got the most pupils within educational institutions and this institution occupies the most educatiors. After-school care centres make a part between education at school and in the family. Specifity of the centres is in procuring of leisure activities of pupils and meaningful using of time. Target group of children in after-school care centres is, within technical education, a neglected target group, that have a great potential at disposal from the point of view of increasing children´s and public interest in science and technology. This article is engaged in the possibility to influence teenagers to prefer positive impacts of technologies.
Keywords: after-school care centres; leisure time; technical education; leisure activities.